(untitled) (Medico Legal Update, 2021)
Objective: To rule out theimpact of resistanceand aerobic exerciseson sugar level in the blood in type 2 diabetes mellitus population. Sample: 10 subjects who have type 2 diabetes mellitus comes under this study. Method: 10 subjects having type 2 diabetes mellitus were taken to control and experimental sets. Experimental set received aerobic and resistance exercise training program as well as medication while control set received only medication for 4 weeks (6 weeks per day). Results: Paired t-test was used, and it was found that blood sugar was reduced in experimental set and two sample t-test was used to check between the group analyses and between set comparison it was found that there was no significant difference detected in sugar level in the blood. Conclusion: It was concluded that resistanceand aerobic exercises are beneficial for lowering the blood glucose level in type 2 diabetes mellitus population.